Демонстративите во „Бомбите“: од единици на референцијата до партикули - Дучевска, Анета; Карапејовски, Бобан (Arizona State University, 2022)
The dual character of the demonstratives in terms of their reference function is the basis for the main hypothesis in this paper. Namely, the demonstratives operate both in the exophoric and endophoric environment, where the antecedent could be recovered in a more associated way or a more explicit one, respectively. This is true especially for the demonstrative pronouns (Macedonian: тој/овој/оној), but also for the demonstrative adjectives (Macedonian: таков/ваков/онаков) and demonstrative adverbs (Macedonian: толку/тука/овде/сега/така). Moreover, their occurrence as deictic markers makes the scope even more interesting and worth analyzing. This being the starting point of the research, the authors have limited the corpus to the so called ‘bombs’, i.e. wiretapped conversations most from the “political elite connected with the then-ruling party” (Friedman 2019, 52), in which an everyday way of conversation is mirrored, so we can say that they can be used as a paradigm to an informal style, or the everyday use of the language. Among other findings, the analysis showed that very often the demonstratives are stripped from their primary functions and are used as affective modals or particles, or discourse markers.